TINGKAT PARTISIPASI MASYARAKAT DI KOTA PONTIANAK DALAM MENGISI WAKTU LUANG DENGAN BEROLAHRAGA - Jumiati, Jumiati; Haetami, Mimi; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this study: the low utilization of leisure time as a means to realize the active lifestyle of the people of Pontianak City in supporting the human development index (HDI). The purpose of this study was to find out how much the level of community participation in filling free time by exercising. The method used in this research is descriptive method with survey techniques with quantitative descriptive forms. The population in this research is the people in Pontianak City with male / female categories whose work schedules are regular. Sampling in this study was rondom sampling, with a total of 100 people. Sampling using the instrument used is a questionnaire sheet. Based on the calculation results, the conclusions data are as follows: The level of community participation in the city of Pontianak in leisure time by exercising is in the high category of 9%, and the category is quite 91%. Keywords: Community participation, Leisure time, Sports.